PERSPECTIVES OF FACTORIAL ANALYSIS IN STUDYING ASSOCIATIONS BETWEEN IMMUNE SYSTEM PARAMETERS AND CLINICAL CHARACTERISTICS IN GASTRIC CANCER - I. G. Solovyeva; L. V. Shcherbakova; V. S. Kozhevnikov; V. V. Abramov; V. A. Kozlov (Медицинская иммунология)
When studying functional features of immune system, a lot of quantitative and functional parameters are determined. A multifactorial analysis allows of detecting interdependent immunological parameters and defining them as significant factors. In present study, four factors are revealed, which are associated with certain clinical characteristics of gastric cancer (tumor invasion depth, lymph node status and distant metastases, tumor stage, histological type). The data obtained are of interest, with regard of systemic approach to functional studies of immune functions.